MOOC-Based Digital Teaching Materials with a Case Method Approach for Improving Students’ Understanding of Hindu–Buddhist Kingdom History - Agustinova, Danu Eko; Aman, A (AL-ISHLAH: Jurnal Pendidikan, 2026)
Digital teaching materials are increasingly needed to support flexible and interactive history learning in higher education. However, the integration of MOOC-based learning with case method pedagogy remains limited, particularly in topics related to the Hindu–Buddhist Kingdoms in Indonesia. This study employed a research and development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed product was a MOOC-based digital teaching material that integrated historical content, visual media, maps, infographics, simulations, and case-based exercises. The implementation involved 33 students from History Education study programs in state universities in the Yogyakarta and Semarang regions. Data were collected through observation, interviews, focus group discussions, documentation, and pretest-posttest assessments. The quantitative data were analyzed using the Shapiro–Wilk normality test and the Wilcoxon Signed-Rank Test. The findings showed an increase in students’ learning outcomes after the intervention. The mean pretest score was 70.00, while the mean posttest score increased to 83.06. The Wilcoxon Signed-Rank Test indicated a statistically significant difference between pretest and posttest scores (p 0.05), suggesting improved understanding of the Hindu–Buddhist Kingdom material after using the MOOC-based digital teaching materials. The findings indicate that MOOC-based digital teaching materials integrated with the case method have potential as an alternative instructional resource for history learning in higher education. However, this study measured learning outcomes rather than critical thinking or 4C skills directly. Further studies using control groups and validated instruments are needed to examine broader competency development.